Modern Radiological Postoperative Diagnostics of the Hip Joint in Children and Adults - Weber, M.-A.; Egermann, M.; Thierjung, H.; Kloth, J. K. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
The assessment of bone healing and loosening of endoprosthesis material was long the primary indication for postoperative projection radiography and CT imaging of the hip joint following trauma and endoprosthesis implantation. With the increasing number of joint-preserving surgery, e. g. of surgical hip luxation and hip arthroscopy for the treatment of femoroacetabular impingement (FAI), high-resolution imaging of intra-articular pathologies before and after surgery has become increasingly important. In this review article, diagnostic imaging of the hip joint is presented following common trauma surgery and orthopedic surgery interventions. The imaging modalities of projection radiography, CT and MRI including direct MR-arthrography are discussed with regard to their diagnostic capability in the postoperative assessment of the hip joint. Among others topics, imaging is discussed following hip arthroplasty, following surgical hip luxation and arthroscopic interventions for the treatment of FAI, as well as following core decompression for avascular necrosis of the femoral head. Moreover, orthopedic interventions of the hip joint in children and adolescents are presented and the dedicated reporting of postoperative imaging is outlined.Key points:• Consolidation of osteotomies and position of implants should be assessed in postoperative imaging.• MRI is useful for confirming correct articulation after treatment of congenital hip dislocation.• Radiologically assessable complications after total hip replacement are inlay wear, loosening, dislocation, periarticular ossifications and infection.• MRI can detect and classify pseudotumours in cases of metal-metal pairing after total hip replacement.Citation Format:• Weber MA, Egermann M, Thierjung H et al. Modern Radiological Postoperative Diagnostics of the Hip Joint in Children and Adults. Fortschr Röntgenstr 2015; 187: 525 – 542
Keywords: hip joint; surgery; postoperative imaging; joint replacement; osteonecrosis; developmental dysplasia of the hip